2012
DOI: 10.1038/ncomms1804
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mutations in NEP compensate for defective H5N1 RNA replication in cultured human cells

Abstract: Infection of mammals by avian influenza viruses requires adaptive mutations to achieve high-level replication in the new host. However, the basic mechanism underlying this adaptation process is still unknown. Here we show that avian polymerases, lacking the human signature PB2-E627K, are incapable of generating usable complementary RnA templates in cultured human cells and therefore require adaptation. Characterization of the highly pathogenic human H5n1 isolate A/Thailand/1(KAn-1)/2004 that retained the avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
173
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 32 publications
20
173
0
Order By: Relevance
“…Despite recent developments, the exact mechanism for this host-specific restriction by PB2 627 remains unclear. It has been suggested that position 627-dependent restriction is due to an incompatibility with a host intracellular protein(s) that results in synthesis of a dysfunctional cRNA template and thus blocks viral RNA replication (27).…”
mentioning
confidence: 99%
“…Despite recent developments, the exact mechanism for this host-specific restriction by PB2 627 remains unclear. It has been suggested that position 627-dependent restriction is due to an incompatibility with a host intracellular protein(s) that results in synthesis of a dysfunctional cRNA template and thus blocks viral RNA replication (27).…”
mentioning
confidence: 99%
“…Known adaptive mutations in NEP of H5N1 human isolates are localized at its Nterminus (M16I, Y41C) as well as at C-terminus (E75G) even in viruses without E627K mutation in PB2. Th ey stimulate the vRNA synthesis mediated by avian IAV polymerase in human cells, enabling to overcome the polymerase restriction in humans (Mänz et al, 2012).…”
Section: Other Iav Proteins Infl Uencing the Virulencementioning
confidence: 99%
“…Therefore, viruses with mutations that facilitate efficient transmission and replication in humans could cause a pandemic. Many amino acid substitutions have been shown to contribute to the adaptation of avian H5N1 viruses to mammalian hosts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In particular, the PB2, PB1, and PA subunits of the polymerase complex play a role in virus pathogenicity and efficient viral growth in mammals.…”
mentioning
confidence: 99%